Extending the LTE-Sim Simulator with Multi-Band Scheduling Algorithms for Carrier Aggregation in LTE-Advanced Scenarios - Robalo, Daniel (2015)
Carrier Aggregation (CA) has been proposed by 3GPP LTE-Advanced to meet or even exceed IMT-Advanced systems enhanced peak data rates requirements. In its rationale, multiple Component Carriers (CC) can be flexibly aggregated so that user equipment can access a total bandwidth of up to 100 MHz. As each CC has the same structure as the one from LTE R8, CA does not require notable changes in the LTE physical layer structure. Nevertheless, the way radio resources are allocated to mobile users in CA scenarios is still an hot research topic and the availability of an open source tool modelling such kind of feature is highly demanded in both academia and industry contexts. The present contribution is three-folded. First, it presents an open source and freeware extension of the well-known LTE-Sim simulator, which implements CA functionalities. Second, it also proposes an implementation of multi-band scheduling strategies able to optimally distribute radio resource among mobile users in the presence of multiple CCs and strict Quality of Service (QoS) constraints. Third, computer simulations have been also carried out to demonstrate the effectiveness of the aforementioned contributions. In particular, simulation results show the capacity improvements achieved by the proposed Enhanced Multi Scheduler against systems without CA, considering values of the bandwidth per component carrier of 5 and 20 MHz, in terms of average cell packet loss, delay, goodput and spectral efficiency.